Surveillance of potential associations between occupations and causes of death in Canada, 1965-91. Issue 4 (1st April 1999) - Aronson, K J; Howe, G R; Carpenter, M; Fair, M E
Abstract : OBJECTIVE: To detect unsuspected associations between workplace situations and specific causes of death in Canada. METHODS: An occupational surveillance system was established consisting of a cohort of 457, 224 men and 242, 196 women employed between 1965 and 1971, constituting about 10% of the labour force in Canada at that time. Mortality between 1965 and 1991 has been determined by computerised record linkage with the Canadian mortality database. Through regression analysis, associations between 670 occupations and 70 specific causes of death were measured. RESULTS: There were almost 116, 000 deaths among men and over 26, 800 deaths among women. About 28, 000 comparisons were made between occupations and specific causes of death. With various reporting criteria, several potential associations were highlighted, including: infectious disease mortality among barbers and hairdressers; laryngeal cancer among male metal fitters and assemblers; lung cancer among female waiters; breast cancer among female metal fitters and assemblers; brain cancer among female nursing assistants and male painters; and ischaemic heart disease among female inspectors and foremen and among male taxi drivers and chauffeurs. CONCLUSIONS: When excess risk of mortality is apparent, the intention of this occupational surveillance system is to spark further studies to gain aetiological knowledge.